Production of soluble pMHC-I molecules in mammalian cells using the molecular chaperone TAPBPR. Issue 12 (29th July 2020) - O'Rourke, Sara M; Morozov, Giora I; Roberts, Jacob T; Barb, Adam W; Sgourakis, Nikolaos G
Abstract: Current approaches for generating major histocompatibility complex (MHC) Class-I proteins with desired bound peptides (pMHC-I) for research, diagnostic and therapeutic applications are limited by the inherent instability of empty MHC-I molecules. Using the properties of the chaperone TAP-binding protein related (TAPBPR), we have developed a robust method to produce soluble, peptide-receptive MHC-I molecules in Chinese Hamster Ovary cells at high yield, completely bypassing the requirement for laborious refolding from inclusion bodies expressed in E.coli . Purified MHC-I/TAPBPR complexes can be prepared for multiple human allotypes, and exhibit complex glycan modifications at the conserved Asn 86 residue. As a proof of concept, we demonstrate both HLA allele-specific peptide binding and MHC-restricted antigen recognition by T cells for two relevant tumor-associated antigens. Our system provides a facile, high-throughput approach for generating pMHC-I antigens to probe and expand TCR specificities present in polyclonal T cell repertoires.